The effect of renal function on the clinical outcomes and management of patients hospitalized with hyperglycemic crises - Almohareb, Sumaya N.; Aljammaz, Norah; Yousif, Nada; Sunbul, Mayar; Alsemary, Raghad; Alkhathran, Lama; Aldhaeefi, Mohammed; Almohammed, Omar A.; Alshaya, Abdulrahman I. (Frontiers in Endocrinology, 2025)
BackgroundThe global prevalence of diabetes has been rising rapidly in recent years, leading to an increase in patients experiencing hyperglycemic crises like diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS). Patients with impaired renal function experience a delay in insulin clearance, complicating the adjustment of insulin dosing and elevating hypoglycemia risk. Accordingly, this study aims to evaluate the impact of renal function on the safety and efficacy of insulin use in patients with isolated DKA or combined DKA/HHS.MethodsA retrospective observational study was conducted at King Abdulaziz Medical City, Saudi Arabia, from January 2016 to December 2021. Eligible patients were ≥18 years, had a confirmed diagnosis of isolated DKA or combined DKA/HHS, presented with an anion gap (AG) of ≥ 16 mmol/L, and received insulin either via continuous infusion or as bolus doses. Patients were categorized into normal kidney function and patients with chronic kidney disease (CKD). The primary outcome was to determine the difference in time to close the AG between the two groups. Statistical analyses were performed using SAS® software.ResultsOut of 319 screened patients, 183 patients met the inclusion criteria. The patients were divided into normal kidney function (43.2%) and CKD (56.8%) groups. The average eGFR for patients with normal kidney function was 93.7 ± 32.5 mL/min/1.73m2 compared to 33.4 ± 14.3 mL/min/1.73m2 for patients with CKD. The time to close AG was similar between patients in the normal kidney function and CKD groups (22.6 ± 16.0 hours vs. 24.5 ± 17.5 hours, p=0.4475). However, the patients’ length of stay in hospital (3.4 ± 2.5 days vs. 5.2 ± 4.0 days; p=0.0004) and ICU (2.5 ± 1.8 days vs. 4.0 ± 2.8 days; p=0.0453) were both significantly longer for patients with CKD. Hypoglycemic events were low in our study with only four documented cases among patients with CKD.ConclusionThis study provides insights into DKA management and outcomes in patients with normal and impaired renal function. The time required to close AG was comparable between the two groups. Larger, multi-center studies are needed to validate these findings and explore additional factors that may impact the management of DKA in patients with CKD.